Ethanolic Extract of Moringa oleifera Leaves Improves Glucose Tolerance, Glycogen Levels, and Liver Health in Alloxan-Induced Diabetic Rats - Qurratu Aini; Samingan Samingan; Mustafa Sabri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract: This study aims to determine the effect of the leaf ethanol extract of (Moringa oleifera L.) on increasing the content of liver glycogen grains in hyperglycemic rats. The research was conducted at the Pathology and Pharmacology Laboratory, Department of Veterinary Clinic, Faculty of Veterinary Medicine, Universitas Syiah Kuala. The method used is an experimental method with a completely randomized design consisting of five treatments and five treatmenttests. Treatment A = Negative control (given with distilled water and physiological NaCl), B = Positive control (75 mg/kg BW of alloxan and incubated for 21 days), C (75 mg/kg BW of alloxan and 150 mg/kg BW of Moringa oleifera leaf ethanol extract for 21 days), D (75 mg/kg of alloxan and 300 mg/kg of Moringa oleifera leaf ethanol extract for 21 days), and E (75 mg/kg of alloxan and 450 mg/kg of Moringa oleifera leaf ethanol extract for 21 days). The parameters observed werethree factors: blood sugar levels, glycogen levels, and histological images of the liver depicting the condition of either a healthy or diseased liver. The results of statistical analysis showed that there was a significant effect, namely that the administration of Moringa oleifera leaf extract at a dose of 450 mg/kg BW was able to reduce blood glucose levels, increase liver glycogen content,and repair liver cell damage in hyperglycemic rats (P<0.01).Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh pemberian ekstrak daun kelor (Moringa oleifera) terhadap peningkatan kandungan butir glikogen hati pada tikus hiperglikemik. Pelaksanaan penelitian dilakukan di Laboratorium Patologi dan Farmakologi Jurusan Klinik Veteriner Fakultas Kedokteran Hewan Universitas Syiah Kuala. Metode yang digunakan adalah metode eksperimen dengan Rancangan Acak Lengkap yang terdiri atas lima perlakuan dan lima ulangan. Perlakuan A = Kontrol negatif (diberi akuades dan NaCl fisiologis), B= Kontrol positif (75 mg/kg BB aloksan dan diinkubasi selama 21 hari), C (75 mg/kg BB aloksan dan 150 mg/kg BB ekstrak daun kelor selama 21 hari), D (75 mg/kg BB aloksan dan 300 mg/kg BB ekstrak daun kelor selama 21 hari), dan E (75 mg/kg BB aloksan dan 450 mg/kg BB ekstrak daun kelor selama 21 hari). Parameter yang diamati adalah kadar glukosa darah, kandungan butir glikogen hati dan perbaikan sel hati pada tikus hiperglikemik. Hasil analisis statistik menunjukkan adanya pengaruh yang signifikan yaitu pemberian ekstrak daun kelor (Moringa oleifera) pada dosis 450 mg/kg BB mampu menurunkan kadar glukosa darah, meningkatkan kandungan butir glikogen hati dan memperbaiki kerusakan sel hati pada tikus hiperglikemik (P<0.01).